ANALISIS MINAT BELI DAN KEPUTUSAN PEMBELIAN MELALUI PRODUCT DAN PRICE - Sebastian, Jenny Ivana; Widyastuti, Maria (UNIKA Santo Thomas, 2023)
The Covid-19 virus pandemic has had an impact on the business world where one of those that has felt the impact of the Covid-19 pandemic is the hotel and tourism industry in Surabaya. The government is anticipating an increase in the Covid-19 pandemic by imposing New Normal, including in Surabaya. This implementation has made the hospitality industry, which initially declined due to Covid-19, is now experiencing an increase. One of them is the Mercure Surabaya Grand Mirama Hotel. This hotel has experienced a decrease in the number of consumers in 2020 and 2021, but consumers will increase in 2022. The research objective is to analyze buying interest and purchasing decisions at the Mercure Surabaya Grand Mirama Hotel through product and price. The results of data processing prove that all statement items are valid, and all variables are reliable. The results of the study show that buying interest and purchasing decisions at the Mercure Surabaya Grand Mirama Hotel through product and price are said to be moderate. The next results show buying interest and purchasing decisions due to product and price, while buying interest is not the cause of purchasing decisions at the Mercure Hotel Surabaya Grand Mirama.